Global Green Diplomacy Cross-Border Collaboration in Mangrove Conservation as a Blue Carbon Solution - LAKSMI, Putu Ayu Sita; PUTRA, I Ketut Johny Pramananda; KUSUMA, A.A Made Indra Wijaya; BAKAR, Mohd Azlan Bin Abu; AGASTIRA, Gusti Ngurah Danan (PT Keberlanjutan Strategis Indonesia, 2025)
The existential challenge of climate change demands urgent solutions, with mangrove conservation emerging as a potent nature-based strategy through the Blue Carbon paradigm. This article explores the transformative concept of